Interior design illustrated - Ching, Francis D. K. , 1943-; Binggeli, Corky
"This book introduces complex concepts of interior design -- from defining interior space, elements and vocabulary of interior design to explaining interior environmental systems -- through his inimitable approach using words and drawings"-- Providedby publisher